2019
DOI: 10.4269/ajtmh.19-0558
|View full text |Cite
|
Sign up to set email alerts
|

Direct Estimation of Sensitivity of Plasmodium falciparum Rapid Diagnostic Test for Active Case Detection in a High-Transmission Community Setting

Abstract: Community-based active case detection of malaria parasites with conventional rapid diagnostic tests (cRDTs) is a strategy used most commonly in low-transmission settings. We estimated the sensitivity of this approach in a hightransmission setting in Western Kenya. We tested 3,547 members of 912 households identified in 2013-2014 by index children with (case) and without (control) cRDT-positive malaria. All were tested for Plasmodium falciparum with both a cRDT targeting histidine-rich protein 2 and with an ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 48 publications
1
16
4
Order By: Relevance
“…We confirmed that transmission intensity remained low in Kap-Kip [17,31], where asymptomatic P. falciparum parasitemia was rarely detected by varATS qPCR (0.22% prevalence), and established that high malaria transmission occurs in Ajigo, where 42% of individuals had asymptomatic parasitemia. Webuye demonstrated moderate transmission with 10% prevalence of asymptomatic parasitemia, which is lower than what has been previously described at this site [32,33], possibly reflecting micro-heterogeneity or seasonal differences, as our study was performed during months when rainfall is historically lower in western Kenya.…”
Section: Discussioncontrasting
confidence: 75%
“…We confirmed that transmission intensity remained low in Kap-Kip [17,31], where asymptomatic P. falciparum parasitemia was rarely detected by varATS qPCR (0.22% prevalence), and established that high malaria transmission occurs in Ajigo, where 42% of individuals had asymptomatic parasitemia. Webuye demonstrated moderate transmission with 10% prevalence of asymptomatic parasitemia, which is lower than what has been previously described at this site [32,33], possibly reflecting micro-heterogeneity or seasonal differences, as our study was performed during months when rainfall is historically lower in western Kenya.…”
Section: Discussioncontrasting
confidence: 75%
“…gDNA was extracted from mosquito abdomens and DBS samples using a Chelex-100 protocol 65 . gDNA from each DBS and mosquito was tested in duplicate using a duplex TaqMan real-time PCR (quantitative PCR (qPCR)) assay targeting the P. falciparum pfr364 motif and the human β-tubulin gene 66 . Samples were defined as P. falciparum positive if: (i) both replicates amplified P. falciparum and both Ct values were <40 or (ii) 1 replicate amplified P. falciparum and Ct value was <38.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies that detected asymptomatic infections using microscopy also reported an increased short-term hazard of symptomatic illness among children within 9 to 30 days after having an asymptomatic malaria infection ( Le Port et al, 2008 ; Njama-Meya et al, 2004 ). We built upon these studies by detecting asymptomatic infections using qPCR, a highly sensitive method with a low limit of detection ( Taylor et al, 2019 ), in participants of all ages and similarly found that asymptomatic infections have a high probability of being quickly followed by symptomatic illness. The increased short-term hazard could reflect misclassification of a ‘pre-symptomatic’ infection that progressed to symptoms as an asymptomatic exposure ( Njama-Meya et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…People with positive RDT results were treated with Artemether-Lumefantrine (AL). DBS were processed to detect P. falciparum infections by extracting genomic DNA (gDNA) from DBS and then tested in duplicate for P. falciparum parasites using a duplex real-time PCR (qPCR) assay targeting the P. falciparum pfr364 motif and human -tubulin gene (Plowe et al, 1995;Taylor et al, 2019). From each DBS, 3 individual punches were deposited in a single well of a 96-well deep well plate and extracted with Chelex-100 following Saponin and Proteinase K treatments.…”
Section: Study Population Sample Collection and Sample Processingmentioning
confidence: 99%